Pelatihan Pendampingan Google Bisnisku dan Sahabat UMKM Bagi Para Pelaku Usaha UMKM di Desa Kelungkung - Edi Irawan; Rozzy Aprirachman (STIKes Ibnu Sina Ajibarang, 2024)
This community empowerment activity was carried out in Kelungkung Village, Batulanteh District, Sumbawa Regency. Based on the results of the activity community service activities with the theme “Google My Business Assistance Training and Sahabat UMKM to Improve Marketing in the Digital Age for Small and Medium Enterprises in Kelungkung Village, Batulanteh District, Sumbawa Regency. Small and Medium Enterprises in Kelungkung Village, Batulanteh District, Sumbawa Regency” that have been carried out, can be concluded as follows: 1) Participants already have additional marketing through online media and how to use it to market the products of small and medium products in Kelungkung Village through Google My Business and Sahabat UMKM. 2) The participants of small and medium business actors get a method of management techniques on how to marketing products through online media. Small and medium business owners in Kelungkung Village know how to do simple bookkeeping